Spatio-temporal multidimensionality of the Ukrainian organ symphonies: from sound to genre - Kupina, Daryna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2019)
The relevance of the study is because the organ symphonies of Ukrainian composers created at the end of the 20th and the beginning of the 21st centuries have not yet become the subject of a special study. The principal dissimilarity between works with a similar genre name, as well as the growing interest of researchers in the ontological parameters of the symphony genre, makes it possible to endow with the genre-defining functions the ratio of the spatial and temporal characteristics of each symphony for an organ. Main objective of the study is determination of the spatial-temporal parameters of organ symphonies written by Ukrainian composers in the late twentieth and early twenty-first centuries using the example of three works for organ solos united by the symphony's genre name – the Organ Symphony by Y. Lyonko, the “White Symphony” by V. Nazarov and “Symphony of Creation” by S. Ostrova. Methodology of the research: system analysis and comparison of three different organ symphonies, the principles of the asymmetry overcoming by the composers are modeled. The main results and conclusions of the study are that there are three types of concepts of organ symphonies – temporal, spatial and modulating. The time and space of the Ukrainian organ symphonies turns out to be heterogeneous and reflects the views of modern scientific thought about the instability of temporal and spatial parameters of reality, their perceptual dependence. Without breaking with the traditional symphonic concepts, the organ symphonies of Y. Lyonko, V. Nazarov, and S. Ostrova are built on the new principles of interpreting the concept of a symphony as co-sounds. In all analyzed works, symphony as a stable artistic concept ensures the continuity of musical development showing various aspects of life (not just human’s one). The deepening of spatial characteristics occurs primarily with techniques of sonoristics and minimal art. Because of attempts by composers to reveal the metaphysical basis of the name “symphony”, the genre is ontologized, pushing the traditional concept of Man into the background. The basic principles of development are the processes of self-movement of the sound mass, subject to the laws of continuity. The significance of the research is in the perspective of its results to clarify the genre invariant of the organ symphony as a whole, as well as its national identification within the framework of Ukrainian organ music